Pengaruh Penerapan Green Accounting Environmental Performance Dan Environment Cost Terhadap Financial Performance - Nurjannah, Elsa Fitriana (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to examine and analyze the influence of green accounting implementation, environmental performance, and environmental cost on financial performance in companies within the basic materials and energy sectors listed on the Indonesia Stock Exchange. This research employs a descriptive method with a quantitative approach, using a total sample of 111 observations, consisting of 37 companies observed over a three-year period from 2021 to 2023. Green accounting is measured using indicators of environmental costs disclosed annually by each company. Environmental performance is assessed using the PROPER rating awarded by the Ministry of Environment and Forestry, based on predetermined criteria and requirements. Environmental cost is calculated using the environmental cost formula, which includes CSR (corporate social responsibility) expenses and post-tax charges disclosed annually by each company. Financial performance is measured using the profitability ratio, namely ROA (return on assets). The testing was conducted using the E-Views application, starting with the determination of the best model to use, followed by significance testing, and finally hypothesis testing. The results confirm that green accounting, environmental performance, and environmental cost have a significant influence on financial performance